Is the robotic rehabilitation that is added to intensive body rehabilitation effective for maximization of upper extremity motor recovery following a stroke? A randomized controlled study - ŞENOCAK, EMRE; YILDIZ ÖZER, AYSEL (My University, 2023)
Background: Trunk stabilization, which is a factor that directly affects the performance of affected upper-limb movements in stroke patients, is of critical importance in the performance of selective motor control. Aims: This study aimed to investigate the effects on upper-limb motor function of the addition of robotic rehabilitation (RR) and conventional rehabilitation (CR) to intensive trunk rehabilitation (ITR). Methods: A total of 41 subacute stroke patients were randomly allocated to two groups: RR and CR. Both groups received the same ITR procedure. Following ITR, a robot-assisted rehabilitation program of 60 min, 5 days a week, for 6 weeks, was applied to the RR group, and an individualized upper-limb rehabilitation to the CR group. Assessments were made at baseline and after 6 weeks using the Trunk Impairment Scale (TIS), Fugl-Meyer Upper Extremity Motor Evaluation Scale (FMA-UE), and Wolf Motor Function Test (WMFT). Results: Improvements were obtained in the TIS, FMA-UE, and WMFT scores for both groups (p 0.05). The RR group scores were relatively high, but not to a statistically significant. Conclusions: When added to intensive trunk rehabilitation, the robot-assisted systems, which are recommended as a stand-alone therapy method, produced similar results to conventional therapies. This technology can be used as an alternative to conventional methods under appropriate conditions of clinical opportunity, access, time management, and staff limitations. However, when RR is combined with traditional interventions such as intensive trunk rehabilitation, it is essential to investigate if the real effect is due to the robotic rehabilitation or the accumulation of positive effects of excessive movement or force spread associated with trained muscles. Registration: This trial was retrospectively registered in the ClinicalTrials.gov with NCT05559385 registration number (25/09/2022).
Keywords: Tıp; Dahili Tıp Bilimleri; Dermatoloji; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Dermatology; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Psikiyatri; DERMATOLOJİ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; PSYCHIATRY; DERMATOLOGY; CLINICAL NEUROLOGY; Nöroloji (klinik); Psikiyatri ve Ruh Sağlığı; Neurology (clinical); Psychiatry and Mental Health; Conventional rehabilitation; Intensive trunk rehabilitation; Motor function; Robotic rehabilitation; Stroke